Treatment of Hepatitis C Infection in Renal Transplant Recipients: The Long Wait Is Over. Issue 5 (15th March 2016) - Saxena, V.; Terrault, N. A.
Abstract : With the availability of all‐oral direct antiviral drugs, safe and highly effective antivirals are now available to hepatitis C–infected kidney transplant recipients, and early single center experiences confirm excellent tolerability and high rates of viral eradication. See the articles by Kamar et al (page 1474 ) and Sawinski et al (page 1588 ).